Bioengineered Matricaria recutita Extract-Assisted Palladium Nanoparticles for the Congo Red Dye Degradation and Catalytic Reduction of 4-Nitrophenol to 4-Aminophenol - Maqsood Ahmad Malik; Abdulmohsen Ali Alshehri; May Abdullah Abomuti; Ekram Y. Danish; Rajan Patel (Toxics, 2021)
The green chemistry method is the preferred approach for synthesizing metal and metal oxide nanoparticles because of its low toxicity, environmental friendliness, feasibility, and safety to human health compared with other chemical or physical methods. The present work reports the phytogenic synthesis of palladium nanoparticles (PdNPs) using an aqueous extract of Matricaria recutita (Chamomile). The phytochemical-mediated synthesis of PdNPs is an economical and eco-friendly approach without using toxic elements as reducing and capping or stabilizing agents. The UV-visible spectroscopic characterization was initially used to confirm the preparation of PdNPs using an aqueous extract of M. recutita flowers as a bioreductant for the reduction of Pd2+ to Pd0 without using any extra capping and reducing agents. The appearance of surface plasmon resonance (SPR) peak at 286 nm confirmed the formation of M. recutita extract-based PdNPs. Furthermore, the PdNPs were characterized by TEM, SEM, EDX, XRD, XPS, and FTIR to confirm their proper synthesis. The thermogravimetric analysis (TGA) was implemented to interpret the decomposition pattern and thermal stability of as-synthesized PdNPs. The biosynthesized PdNPs were further applied as a nanocatalyst in degradation of an azo dye Congo red (CR) in the presence of NaBH4. The catalytic reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) was also investigated in the presence of NaBH4. All the catalytic reactions were performed in water, and no significant loss in catalytic activity was observed after recovery and reusability of the biosynthesized PdNPs.